Increased breadth of HIV-1 neutralization achieved by diverse antibody clones each with limited neutralization breadth. - Valentine U Chukwuma; Nurgun Kose; D Noah Sather; Gopal Sapparapu; Rachel Falk; Hannah King; Vidisha Singh; Rebecca Lampley; Delphine C Malherbe; Noah T Ditto; Jonathan T Sullivan; Trevor Barnes; et al. (PLoS ONE, 2018)
Broadly neutralizing antibodies (bNAbs) are rarely elicited by current human immunodeficiency virus type 1 (HIV-1) vaccine designs, but the presence of bNAbs in naturally infected individuals may be associated with high plasma viral loads, suggesting that the magnitude, duration, and diversity of viral exposure may contribute to the development of bNAbs. Here, we report the isolation and characterization of a panel of human monoclonal antibodies (mAbs) from two subjects who developed broadly neutralizing autologous antibody responses during HIV-1 infection. In both subjects, we identified collections of mAbs that exhibited specificity only to a few autologous envelopes (Envs), with some mAbs exhibiting specificity only to a subset of Envs within the quasispecies of a particular sample at one time point. Neutralizing antibodies (NAbs) isolated from these subjects mapped mostly to epitopes in the Env V3 loop region and the CD4 binding site. None of the individual neutralizing mAbs recovered exhibited the cumulative breadth of neutralization present in the serum of the subjects. Surprisingly, however, the activity of polyclonal mixtures comprising individual mAbs that each possessed limited neutralizing activity, could achieve increased breadth of neutralizing activity against autologous isolates. While a single broadly neutralizing antibody targeting one epitope can mediate neutralization breadth, the findings presented here suggest that a cooperative polyclonal process mediated by diverse antibodies with more limited breadth targeting multiple epitopes also can achieve neutralization breadth against HIV-1.